Innovative East Asia : (World Bank, 2003)
The salience of East Asia in the global economy is now unquestionable, and with a population of nearly 1.9 billion, its expanding markets will strongly influence the tempo of international trade and the growth of global incomes. However, while the potential of East Asian economies has been amply demonstrated, their future performance is by no means assured